Evaluation of heavy metal content of some lipsticks in Iran market - Hamed Naalbandi; Majid Saeedi; Omid Moharrami Moghanlou; Jafar Akbari; Katayoun Morteza-Semnani; Raouf Alizadeh; Mohammad Hossein Esfahani-Zadeh; Mahgol Tajbakhsh (Mazandaran University of Medical Sciences, 2016)
This study quantitatively estimated heavy metals as cadmium, lead, chromium and nickel (Cd, Pb, Cr and Ni) using flame atomic absorption spectrometry (FAAS) in ten lipstick products sold by local markets in Sari, Mazandaran State, Iran. All the samples were digested in HNO3 and HClO4 and then evaluated for heavy metal contents. All the concentrations are mean value of triplicate experiments for each sample. Analysis of variance (ANOVA) and Tukey post-hoc tests were used to determine significant variations in heavy metal contents and p < 0.05 was considered as significant. The determined range of cadmium, lead, chromium and nickel were 0.01-0.05  𝜇g /g, 0.18-0.80  𝜇g/g, 0.06-0.75 𝜇g/g, and 0.00-0.34 𝜇g/g, respectively. These results showed that nickel and cadmium contents were less than WHO and US FDA safe limit, while for chromium only one samples (No. 5) showed higher concentration than safe limit. The content of lead in all samples were lower than safe limit unless sample 6 which showed high level of lead.